Hippocampal Synthesis of Sex Steroids and Corticosteroids: Essential for Modulation of Synaptic Plasticity - Hojo, Yasushi; Higo, Shimpei; Kawato, Suguru; Hatanaka, Yusuke; Ooishi, Yuuki; Murakami, Gen; Ishii, Hirotaka; Komatsuzaki, Yoshimasa; Ogiue-Ikeda, Mari; Mukai, Hideo; Kimoto, Tetsuya (Frontiers in Endocrinology, 2011)
Sex steroids play essential roles in the modulation of synaptic plasticity and neuroprotection in the hippocampus. Accumulating evidence shows that hippocampal neurons synthesize both estrogen and androgen. Recently, we also revealed the hippocampal synthesis of corticosteroids. The accurate concentrations of these hippocampus-synthesized steroids are determined by liquid chromatography-tandem mass spectrometry in combination with novel derivatization. The hippocampal levels of 17β-estradiol (E2), testosterone (T), dihydrotestosterone (DHT) and corticosterone (CORT), are 5-15 nM, and these levels are sufficient to modulate synaptic plasticity. Hippocampal E2 modulates memory-related synaptic plasticity not only slowly/genomicaly but also rapidly/nongenomically. Slow actions of E2 occur via classical nuclear receptors (ERα or ERβ), while rapid E2 actions occur via synapse-localized or extranuclear ERα or ERβ. Nanomolar concentrations of E2 changes rapidly the density and morphology of spines in hippocampal neurons. ERα, but not ERβ, drives this enhancement/suppression of spinogenesis in adult animals. Nanomolar concentrations of androgens (T and DHT) and CORT also increase in the spine density. Kinase networks are involved downstream of ERα and androgen receptor (AR). Newly developed Spiso-3D mathematical analysis is useful to distinguish these complex effects by sex steroids and kinases. Significant advance has been achieved in investigations of rapid modulation by E2 of the long-term depression or the long-term potentiation.